Relationship between Prostate Volume and International Prostate Symptom Score (IPSS) Degree of Tamed Prostate Enlargement on Transabdominal Ultrasonography (TAUS) and Transrectal Ultrasonography (TRUS) Examination - Azhar, Abu; Eriawan Agung Nugroho; Ezra Endria Gunadi (Fakultas Kedokteran Universitas Sriwijaya (Faculty of Medicine, Universitas Sriwijaya) Indonesia, 2021)
A B S T R A C TIntroduction: IPSS is the gold standard in measuring clinical symptoms of BPH. 1Prostate volume has been said to have a close relationship with the development ofBPH. 9 The aim of this study was to determine the relationship between prostate volumeas measured by transabdominal ultrasonography (TAUS) and transrectal (TRUS) to thedegree of IPSS. Methods: An analytic observational study with a cross sectional designwas carried out on 303 BPH patients at the General Hospital of Kariadi Hospital,Semarang. The data obtained from the TAUS, TRUS and IPSS prostate volume wereobtained from medical records for the period 2015 - 2020. The data were then analyzedby using the chi square test. Results: Patients with BPH have a TAUS prostate volumein classification I of 0 people 0%, classification II of 16 people (5.3%), classification IIIof 96 people (31.7%), classification IV of 102 people (33.7%) and classification V of 89people (29.4%). While TRUS in classification I was 0% (0 people), classification II was11 people (3.6%), classification III was 92 people (30.4%), classification IV was 110people (36.3%) and classification V of 90 people (29.7%). IPSS obtained severe IPSSdegrees, namely 192 people (63.4%), moderate degrees of 111 people (36.6%), and milddegrees 0% (0 people). The results of the Chi Square test obtained a p-value of 0.000(p <0.05), indicating that there was a significant relationship between prostate volume,whether examined by transabdominal or transrectal ultrasound, and the degree ofIPSS. The correlation coefficient r = 0.925 indicates a very strong relationship betweenprostate volume as measured by both transabdominal and transrectal ultrasound withthe degree of IPSS, a positive result shows that the increase in prostate volume, thedegree of IPSS will also increase. Conclusion: There is a significant relationshipbetween prostate volume as measured by both TAUS and TRUS and the degree of IPSS.